2014
DOI: 10.1158/1055-9965.epi-14-0199
|View full text |Cite
|
Sign up to set email alerts
|

HPV Seroconversion Following Anal and Penile HPV Infection in HIV-Negative and HIV-Infected MSM

Abstract: Background: We assessed human papillomavirus (HPV) seroconversion following anal and penile HPV infection in HIV-negative and HIV-infected men who have sex with men (MSM).Methods: MSM aged !18 years were recruited in Amsterdam, the Netherlands (2010-2011), and followed up semiannually. Antibodies against 7 high-risk HPV types in baseline and 12-month serum samples were tested using a multiplex immunoassay. Baseline, 6-, and 12-month anal and penile samples were tested for HPV DNA using the SPF 10 -PCR DEIA/LiP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…In contrast, previous HPV serological surveys of MSM have included older, more sexually experienced men where the great majority of men are found to have prevalent anal HPV infection . Mooij et al . reported data on HPV seroconversion following incident HPV DNA infection in MSM.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, previous HPV serological surveys of MSM have included older, more sexually experienced men where the great majority of men are found to have prevalent anal HPV infection . Mooij et al . reported data on HPV seroconversion following incident HPV DNA infection in MSM.…”
Section: Discussionmentioning
confidence: 98%
“…18 In contrast, previous HPV serological surveys of MSM have included older, more sexually experienced men where the great majority of men are found to have prevalent anal HPV infection. [15][16][17]25,26 Mooij et al 27 reported data on HPV seroconversion following incident HPV DNA infection in MSM. That study included much older MSM (median age: 38 years for HIV-negative MSM, 47 for HIV-positive MSM) where 38% were HIV-infected.…”
Section: Discussionmentioning
confidence: 99%
“…Overall seroconversion rates were highest for HPV6 (19%), whereas only 4% and 3% of men seroconverted within 36 months after infection with HPV16 and HPV18, respectively [51]. Seroconversion rates are slightly higher in HIV-positive MSM compared to HIV-negative heterosexual men (18% vs. 13%, p = 0.1); however, anti-HPV antibody levels are mostly low, leaving men susceptible to recurrent HPV infections [50,51].…”
Section: Hpv Vaccinationmentioning
confidence: 94%
“…This is even more dramatic in men, in whom type-specific seroconversion rates after incident anogenital HPV infection range from 8% to 19% [49][50][51]. The anatomic site of HPV infection and differences in immune response to specific HPV types further affects seroconversion rates [50,51]. A total of 19%, 6%, and 0% of men studied seroconverted to at least one HPV type after incident genital, anal, and oral HPV infection, respectively.…”
Section: Hpv Vaccinationmentioning
confidence: 97%
See 1 more Smart Citation